Students' perception towards Malay folklore songs - Abd Rahim, Normaliza; Harun, Nik Ismail (Springer, 2014)
This study focuses on students’ perception towards Malay folklore songs. The objectives of the study were to identify and discuss students’ perception towards the Malay folklore songs. The samples of the study were 200 subjects from Universiti Putra Malaysia. A set of questionnaires were distributed to the students. The questionnaire consists of students’ perception towards the Malay folklore song. The songs were music arranged by using the modern pop genre and the lyrics were written to ensure the originality of the stories. Five Malay folklore songs were heard in the classroom. The songs entitled, ‘Bird of Paradise’, ‘Why do Crows have Black Feathers?’, ‘Birds’ Leader’, ‘The Mermaid River’ and ‘The Flamingo and the Deer’. The data from the questionnaires were analysed by using the percentage. The results of the study revealed that majority of the subjects strongly agreed and agreed that the lyrics of the songs were simple and well understood, the storylines were interesting and intelligible and also, the music for the songs were suitable and interesting. It is hoped that further study will focus on other Malay folklore songs for students at schools.